DEVELOPMENTAL CHANGES IN THE MORPHOLOGY OF SOME BLOOD VESSELS IN THE FOETUSES OF THE RED SOKOTO GOAT - C.O. Igbokwe; E.C. Muokwah; D.N. Ezeasor (Journal of Animal and Plant Sciences, 2015)
A study of the development of the umbilical cord and aorta was carried out in the Red Sokoto goat in foetal ages of about 30-49 days, 50-98 days and 99-148 days by gross dissection and histology using abattoir specimens. The morphometry of the blood vessels studied showed a steady progressive increase with gestational age. The greatest increase in all the parameters was observed in the third foetal stage (99-148 days). The results obtained showed that the umbilical cord attained a mean length of 39.73cm and a mean diameter of 11.38mm. The foetal aorta gave mean length of 14.49cm and a mean diameter 3.32cm at 99-148 days. Histologically, the umbilical cord in foetal age 30-49 days showed a pair of umbilical arteries and a vein which were still rudimentary in development of its normal features. The developing tunics were present but not yet fully differentiated. During foetal age 50-98days, the vessels maintained the same number and showed further differentiation of the tunics into tunica intima, tunica media and adventitia. The umbilical vessels in foetal age 99-148 days showed marked shrinkage of the tunics, but with a larger lumen. The aorta in foetal age 30-49 days displayed well-developed tunics, with very prominent elastic membranes, abundant smooth muscle cells and few layers of elastic fibers in the tunica intima. The aorta in foetal age 50-98 days showed increase in the layers of the walls. Further increase in the layers of the wall of the aorta was seen in foetal age 99-148 days. Other structural features of the developing foetuses observed in all stages were presence of ductus venosus and ductus arteriosus in the liver and heart respectively. The results of this study showed that the foetal cardiovascular system undergoes adaptive morphological changes with the increase in size and complexity of the developing foetus.
Keywords: Morphology; blood vessels; foetal goat